Creating Child-Friendly Sports Through Sign Systems: Visual Innovation at SDS Sawitan, PT. Bangkitgiiat Usaha Mandiri (BUM) - Novianto, Chabib; Janos, Hevon Pheriantsih; Adriansyah, Fikri; Marshanda, Marshanda; Rahardian, Dwinta Noval; Djohan, Athaya Zafirah; Sevia, Rizka; Purnomo, Azfa Naufal; Andhika, Muhammad; Wijaya, Rama; Novitasari, Dea (Edumedia Solution, 2025)
This community service program aims to implement a child-friendly sign system at SDS Sawitan PT. Bangkit Giat Usaha Mandiri (BUM) to support the Child-Friendly School concept in accordance with the Regulation of the Minister of Women’s Empowerment and Child Protection (PPPA) No. 8 of 2014. The activities were carried out using a participatory method, involving teachers, students, and the KKN team in four stages: planning, production and installation, socialization and education, and evaluation. The signs were designed with bright colors, simple illustrations, and easy-to-understand language, and were printed on safe and weather-resistant materials. As a result, students were able to understand the signs without additional explanations, showed improved orderly behavior and compliance with rules, and required fewer verbal instructions from teachers. Socialization efforts with students and parents extended the educational impact into the home environment. The evaluation indicated the need to adjust the position of several signs to enhance visibility. Overall, this program successfully created a safer, more informative, and conducive learning environment, while instilling values of discipline, cleanliness, and care from an early age. This success underscores the importance of cross-sector collaboration in producing sustainable educational visual solutions for elementary schools.